PROPOSED A DESIGN COMPANY PERFORMANCE MANAGEMENT SYSTEM BY USING INTEGRATED PERFORMANCE MANAGEMENT SYSTEM (IPMS) FRAMEWORK AT PT RIFANSI DWI PUTRA - Boyke F L Simanullang, Yosef
PT Rifansi Dwi Putra is a company that specializes in the field of engineering, procurement and construction in the oil and gas industry. In the field of engineering, procurement and construction, management as one of stakeholders that plays a highly important role in creating an organization or company which is competitive and sustainable, where management is illustrated as a sequence of mechanism that can coordinate a diversity of sources to earn the objectives of the organization or company that has been established. Increasingly the development of the oil and gas industry, especially in Indonesia, which is characterized by increasingly intense competition in the fields of engineering, procurement and construction requires PT Rifansi Dwi Putra can compete with new entrants and current contractors. Hence, we need a system that can help PT Rifansi Dwi Putra in improving and maintaining its performance in order to keep on compete and grow.